2014
DOI: 10.1371/journal.pone.0100787
|View full text |Cite
|
Sign up to set email alerts
|

Open Reading Frame 3 of Genotype 1 Hepatitis E Virus Inhibits Nuclear Factor-κappa B Signaling Induced by Tumor Necrosis Factor-α in Human A549 Lung Epithelial Cells

Abstract: Hepatitis E virus (HEV) is one of the primary causative agents of acute hepatitis, and represents a major cause of severe public health problems in developing countries. The pathogenesis of HEV is not well characterized, however, primarily due to the lack of well-defined cell and animal models. Here, we investigated the effects of genotype 1 HEV open reading frame 3 (ORF3) on TNF-α-induced nucleus factor-κappa B (NF-κB) signaling. Human lung epithelial cells (A549) were transiently transfected with ORF3 contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…The ORF3 of HEV encodes a phosphoprotein that can play a critical role in regulating a series of host cell processes to create an immunosuppressive environment suitable for virus survival and persistent infection . Our previous study showed that the HEV ORF3 could obviously inhibit the secretion of inflammation factors of macrophages by inhibiting the activation of nuclear factor κ‐light‐chain‐enhancer of activated B‐cells pathway .…”
Section: Discussionsupporting
confidence: 91%
“…The ORF3 of HEV encodes a phosphoprotein that can play a critical role in regulating a series of host cell processes to create an immunosuppressive environment suitable for virus survival and persistent infection . Our previous study showed that the HEV ORF3 could obviously inhibit the secretion of inflammation factors of macrophages by inhibiting the activation of nuclear factor κ‐light‐chain‐enhancer of activated B‐cells pathway .…”
Section: Discussionsupporting
confidence: 91%
“…ORF2 encodes a 72-kDa protein that forms the capsid. ORF3 encodes a small multifunctional protein (12)(13)(14)(15). Although originally recognized as a nonenveloped virus, recent studies show that HEV circulating in blood is cloaked in host membranes (16).…”
mentioning
confidence: 99%
“…Certain TNF‐α and IFN‐γ gene promoter polymorphisms, which seem to be associated with higher cytokine production, seem to be associated with higher susceptibility for HEV infections (‐308‐AA in promoter region) or severe symptomatic disease (TNF‐1031CC and IFN‐874TT) . HEV ORF‐3 inhibits TNFα‐induced nuclear factor‐kappa B signalling . Therapy with TNF‐α inhibitors for rheumatologic conditions has been associated with HEV infection .…”
Section: Host Factorsmentioning
confidence: 76%
“…36 HEV ORF-3 inhibits TNFα-induced nuclear factorkappa B signalling. 37 Therapy with TNFα inhibitors for rheumatologic conditions has been associated with HEV infection. 9 Though most of these have been acute infections, chronic HEV has been described, despite anti-HEV T-cell responses being preserved, with use of these agents.…”
Section: Il-1ra Stimulates Type III Ifn By Plasmacytoid Dendritic Celmentioning
confidence: 99%